2015
DOI: 10.1038/nnano.2015.38
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in art conservation

Abstract: Tackling the degradation of cultural heritage requires a global effort. We call on all material scientists to develop new nanomaterials and methods for the preservation of artwork.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(121 citation statements)
references
References 23 publications
3
109
0
Order By: Relevance
“…Alongside DAP, also ammonium dihydrogen phosphate (ADP) and ammonium phosphate (AP) have been investigated as precursors [9,10]. However, since the main difference between these phosphate salts is their speciation in PO 4 3-, HPO 4 2-and H 2 PO 4 -ions and since the relative amount of these species actually depends on the solution pH, the nature of the phosphate precursor is basically irrelevant, as long as the pH of the phosphate solution is controlled [9].  pH of the phosphate solution.…”
Section: Treatment Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside DAP, also ammonium dihydrogen phosphate (ADP) and ammonium phosphate (AP) have been investigated as precursors [9,10]. However, since the main difference between these phosphate salts is their speciation in PO 4 3-, HPO 4 2-and H 2 PO 4 -ions and since the relative amount of these species actually depends on the solution pH, the nature of the phosphate precursor is basically irrelevant, as long as the pH of the phosphate solution is controlled [9].  pH of the phosphate solution.…”
Section: Treatment Conditionsmentioning
confidence: 99%
“…DAP concentrations ranging from 0.1 M [9,11] up to 3 M (close to saturation) have been explored [7,12]. The motivation to use highly concentrated solution is that only a minor fraction (<1%) of ions originated from DAP dissociation are PO 4 3-ions (needed to form HAP), whereas the largest part is in the form of HPO 4 2- [9]. However, when highly concentrated DAP solutions are used, the formed calcium phosphate films tend to crack because of an excessive thickness.…”
Section: Treatment Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gels have been used for years in conservation to remove surface contamination from works of art in a localized and selective way. A gel confines the action of a solvent or cleaning agent to the area of the object with which it is in contact, preventing the spread of any material-either the cleaning agents or the materials targeted for removal-through and across the artwork (Carretti et al 2010;Baglioni et al 2015). For SERS applications, a gel could substitute the colloid drop traditionally used as the medium for the target dye and the plasmonic nanoparticles to interact; alternatively, a gel loaded with appropriate reagents could be used to perform a mild extraction of the target analyte from its substrate, for subsequent analysis with a silver colloid deposited on the gel.…”
Section: Detachable Sers Substratesmentioning
confidence: 99%
“…), and their low solvent content reduces the environmental impact. In fact, throughout the last decade, nanostructured fluids have been widely tested for the cleaning of mural paintings, and the results obtained have demonstrated that these systems are a valid alternative to the use of neat solvents [8][9][10][11]. However, for their use on watersensitive substrates, o/w microemulsions must be confined within a retentive network that allows their controlled release, so as to grant the removal of unwanted layers without excessive wetting of the surface.…”
Section: Introductionmentioning
confidence: 99%